Practice environment and work-related quality of life among nurses in a selected hospital in Zamboanga, Philippines: A correlational study - Jan Paolo Barandino; Gil Soriano (Tehran University of Medical Sciences, 2019)
Background & Aim: Nurses often work in problematic work environments, characterized by various difficulties and stress-factors that can undermine nurses' full capacity to provide excellent care. In addition, the nurse practice environment can have an impact on the quality of work life, nurse recruitment and retention and quality patient outcomes. Thus, the study assessed the relationship between practice environment and work-related quality of life as perceived by nurses in a selected hospital in Zamboanga City, Philippines. Methods & Materials: A descriptive correlational design was used in the study and the total population of nurses were recruited as participants.  The Practice Environment Scale of the Nursing Work Index and Work-Related Quality of Life Scale were used to gather the needed data. Data were analyzed using mean, standard deviation and spearman rank-order correlation. Results: A total of 103 nurses were surveyed in the study. In the perceived practice environment scale, it was revealed that the nursing foundation for quality of care was the highest (M=3.01, SD=0.20) and staffing and resource adequacy was the lowest (M=2.56, SD=0.45). On the other hand, job career satisfaction was the highest (M=3.64, SD=0.57) and stress at work was the lowest (M=2.55, SD=0.22) in the perceived work-related quality of life scale. The study showed a significant relationship between the perceived practice environment and perceived the work-related quality of life (rho=0.287, p=0.003). Conclusion: The study revealed that nurses have a favorable work related quality of life and practice environment. However, formulating and enhancing programs for nurses such as incentive and professional development should be done as this can help foster and sustain a positive practice environment and job satisfaction.